2020
DOI: 10.3390/en13112941
|View full text |Cite
|
Sign up to set email alerts
|

Porous Cores in Small Thermoacoustic Devices for Building Applications

Abstract: The thermoacoustic behavior of different typologies of porous cores is studied in this paper with the goal of finding the most suitable solution for small thermoacoustic devices, including solar driven air coolers and generators, which can be used in future buildings. Cores provided with circular pores, with rectangular slits and with arrays of parallel cylindrical pins are investigated. For the type of applications in focus, the main design constraints are represented by the reduced amount of the input heat p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…This conclusion is consistent with the findings in studies [157][158][159][160]. As to the geometry of the stack, it is found that the pin array configuration outperforms the parallel-plate or circular-pore ones [161][162][163][164], and the optimal pore size is when rh/δk is between 1.0 and 1.5 [165][166][167]. Regarding the working gas, research has found that the mean pressure has an optimal value since it affects rh/δk [168][169][170].…”
Section: Standing-wave Thermoacoustic Systemssupporting
confidence: 88%
“…This conclusion is consistent with the findings in studies [157][158][159][160]. As to the geometry of the stack, it is found that the pin array configuration outperforms the parallel-plate or circular-pore ones [161][162][163][164], and the optimal pore size is when rh/δk is between 1.0 and 1.5 [165][166][167]. Regarding the working gas, research has found that the mean pressure has an optimal value since it affects rh/δk [168][169][170].…”
Section: Standing-wave Thermoacoustic Systemssupporting
confidence: 88%
“…Based on the acoustic field, TAEs can be classified into standing-wave and travellingwave types [8][9][10]. Standing-wave TAEs rely on imperfect heat conduction to realize Brayton-like thermodynamic cycles within the boundary layers [11][12][13] whereas travelling-wave TAEs require perfect heat conduction to execute Stirling-like cycles [14][15][16]. Although standing-wave TAEs are less efficient from a thermodynamic perspective, they are simple in structure, compact in size and, most importantly, cheap to fabricate, therefore remaining competitive with their travelling-wave counterparts regarding cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Some efforts include usage of wet stack or regenerator [30,31], random stack configuration [32], converging stack design [33] and various stack plate edge profiles/shapes [34]. Recently, Auriemma et al conducted a numerical study to compare the performance of stacks with different geometries for building applications [35].…”
Section: Introductionmentioning
confidence: 99%